Kepatuhan Tenaga Kesehatan dalam Penggunaan Sarung Tangan Non Steril - Puspariani, Ni Komang Sri; Kamaryati, Ni Putu; Rahayuni, IGA Rai; Kusuma, Made Dian Santi (Journal of Telenursing (JOTING), 2023)
This study aims to identify factors that influence compliance with the use of non-sterile gloves among health workers. The method used is a literature review. There are ten articles obtained from online databases on Pubmed, Science Direct, and other sources. Articles were selected using PRISMA and article appraisal. The results of this study show that health workers use gloves not in accordance with guidelines such as not carrying out hand hygiene before and after using gloves, using gloves more often than necessary, and failing to remove or change gloves at the right time. Factors that encourage health workers to wear non-sterile gloves are personal protection, patient protection, motivation to create a professional image and follow in the footsteps of seniors. Meanwhile, misuse and non-compliance with the use of gloves is influenced by a lack of knowledge and situational understanding of indications for use, age, gender, discomfort due to the use of PPE, lack of availability and access to PPE, attitude of health workers, and lack of supervision. In conclusion, health workers' compliance in using gloves can be improved with health education about controlling and preventing the spread of disease, training and refreshers in the proper use of PPE, supervision and management support to increase the availability and accessibility of PPE. Keywords: Compliance, Non-Sterile Gloves, Health Workers